Strategi Pembelajaran Concept Mapping dengan Media CD Pembelajaran untuk Meningkatkan Kualitas Pembelajaran PKn - Maulidin Nur Secha; Nur Fajrie; Sri Surachmi W (Journal on Education, 2023)
The results of initial observations in class IV at SDN Gunungpati 03 show that learning is less meaningful and student learning outcomes are not optimal. There were 17 students out of 27 students or 60% of their learning outcomes had not reached the minimum completeness criteria (KKM). The research objective was to improve student learning outcomes in Civics subjects using Concept Mapping learning strategies with learning CD media. This type of research is classroom action research (CAR) by applying two cycles. The teacher has implemented a Concept Mapping learning strategy with learning CD media properly and optimally. The results of the students' formative tests showed that the learning completeness after the research was carried out increased by 42%, that is, from 40% to 82%. The conclusion from this study is that the use of Concept Mapping learning strategies with CD media can improve student learning outcomes in class.